Inflammation of brown/beige adipose tissues in obesity and metabolic disease. (16th July 2018) - Villarroya, F.; Cereijo, R.; Gavaldà‐Navarro, A.; Villarroya, J.; Giralt, M.
Abstract: Many of the comorbidities of obesity, including type 2 diabetes and cardiovascular diseases, are related to the low‐grade chronic inflammation of white adipose tissue. Under white adipocyte stress, local infiltration of immune cells and enhanced production of pro‐inflammatory cytokines together reduce metabolic flexibility and lead to insulin resistance in obesity. Whereas white adipocytes act in energy storage, brown and beige adipocytes specialize in energy expenditure. Brown and beige activity protects against obesity and associated metabolic disorders, such as hyperglycaemia and hyperlipidaemia. Compared to white fat, brown adipose tissue depots are less susceptible to developing local inflammation in response to obesity; however, strong obesogenic insults ultimately induce a locally pro‐inflammatory environment in brown fat. This condition directly alters the thermogenic activity of brown fat by impairing its energy expenditure mechanism and uptake of glucose for use as a fuel substrate. Pro‐inflammatory cytokines also impair beige adipogenesis, which occurs mainly in subcutaneous adipose tissue. There is evidence that inflammatory processes occurring in perivascular adipose tissues alter their brown‐versus‐white plasticity, impair the extent of browning in these depots and favour the local release of vasculature damaging signals. In summary, the targeting of brown and beige adipose tissues by pro‐inflammatory signals and the subsequent impairment of their thermogenic and metabolite draining activities appears to represent obesity‐driven disturbances that contribute to metabolic syndrome and cardiovascular alterations in obesity. Abstract : Content List –14th Key Symposium ‐ "Metabolic Complications of Obesity" .